ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UTANG LUAR NEGERI INDONESIA PERIODE 1985-2020 - Mukhamad Yusuf Iskandar (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Indonesia is one of the developing countries in the Asian continent that uses foreign debt as aid to support the country's economic development, resulting in an increase in Indonesia's foreign debt every year. On the other hand, increasing foreign/external debt is one of the economic problems caused by world economic shocks or when an economic recession is occurring. This study aims to determine the relationship between the variabels of the level of exports, imports, and inflation rates on Indonesia's external debt. The analysis technique used is the Vector Error Correction Model (VECM) with a research period from 1985 to 2020 and using the E-Views 10 application. The test results show that the variabels of exports, imports, and inflation have a significant relationship with external debt in the long term. While the relationship in the short term shows a less significant relationship between these variabels.